COVID-19 and arrhythmia: The factors associated and the role of myocardial electrical impulse propagation. An observational study based on cardiac telemetric monitoring - Cozzolino, Domenico; Romano, Ciro; Nevola, Riccardo; Marrone, Aldo; Umano, Giuseppina R.; Cuomo, Giovanna; Rinaldi, Luca; Adinolfi, Luigi E.; , Vanvitelli COVID Collaborators; Marianna, Abitabile; Domenico, Beccia; Chiara, Brin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. The heart is commonly involved in COVID-19, and rhythm disorders have been largely reported. Objectives. To evaluate the association of some non-cardiac and cardiac comorbidities and of QT dispersion with arrhythmias and their impact on outcome in hospitalized COVID-19 patients. Methods. Each patient underwent cardiac telemetry monitoring through entire hospitalization period, laboratory analyses, 12-lead electrocardiogram, and lung imaging examination. Patients with arrhythmia were divided into three groups (with brady-arrhythmias, with tachy-arrhythmias, and with tachy- and brady-arrhythmias). Results. Two-hundred patients completed the study (males, 123; mean age, 70.1 years); of these, 80 patients (40%) exhibited rhythm disorders on telemetry. Patients with arrhythmia were older (p<0.0001), had greater number of comorbidities (p<0.0001), higher values of creatinine (p=0.007), B-type natriuretic peptide (p<0.0001), troponin (p<0.0001), c-reactive protein (p=0.01), ferritin (p=0.001), d-dimer (p<0.0001), procalcitonin (p=0.0008), QT interval (p=0.002), QTc interval (p=0.04), and QTc dispersion (p=0.01), and lower values of sodium (p=0.03), magnesium (p=0.04), glomerular filtration rate (p<0.0001), and hemoglobin (p=0.008) as compared to patients without arrhythmia. By comparing the three subgroups of patients, no significant differences were found. At multivariate analysis, age (OR=1.14 [95% CI: 1.07-1.22]; p=0.0004), coronary artery disease (OR=12.7 [95% CI: 2.38-68.01]; p=0.005), and circulating troponin (OR=1.05 [95% CI: 1.003-1.10]; p=0.04) represented risk factors independently associated with arrhythmia. All-cause in-hospital mortality was ~forty-fold higher among patients with arrhythmia (OR=39.66 [95% CI: 5.20-302.51]; p=0.0004). Conclusion. Arrhythmias are associated with ageing, coronary artery disease, subtle myocardial injury, hyperinflammatory status, coagulative unbalance, and prolonged QTc dispersion in COVID-19 patients, and confer a worse in-hospital prognosis. Given its usefulness, routinary use of cardiac telemetry should be encouraged in COVID wards.